Customer journey management capability in business-to-business markets: Its bright and dark sides and overall impact on firm performance - Christian Homburg; Moritz Tischer (Journal of the Academy of Marketing Science, 2023)
Business-to-business (B2B) practitioners are increasingly interested in capabilities to holistically manage touchpoints along B2B customer journeys (CJs) to remain competitive. Research in the B2B context, however, has investigated neither what constitutes such a customer journey management capability (CJMC) nor how , whether , or when it creates value. Taking a mixed-methods approach, we conceptualize and operationalize B2B CJMC as a supplier's ability to achieve superior customer value along the B2B CJ by strategically creating value-anchored customer touchpoints characterized through the implementation of consistent resource usage across internal organizational boundaries and by continuously monitoring value creation toward the individual members of the buying center. Analyzing a multisource dataset, we provide evidence that B2B CJMC has an indirect effect on firm performance (i.e., return on sales) through two opposing mechanisms (i.e., customer loyalty and customer-related coordination costs). Importantly, using survey and archival data, we show that, overall, B2B CJMC has a significant and positive impact on firm performance through the two mechanisms. Finally, these underlying mechanisms are also prevalent when testing for the moderating factors switching costs, number of touchpoints, and product versus service.
Keywords: 330; Customer journey management; Dynamic capabilities; Bright side; Dark side; Firm performance; Business-to-business